The Electric Energy Generation Approach of the Energy Saving House Using Photovoltaic System - Al-Douri, A. A.J. (Iraqi Journal of Physics, 2011)
This paper describes a research effort that aims of developing solar models for housing suitable for the Arabian region since the Arabian Peninsula is excelled with very high levels of solar radiation. The current paper is focused on achieving energy efficiency through utilizing solar energy and conserving energy. This task can be accomplished by implementation the major elements related to energy efficiency in housing design , such as embark on an optimum photovoltaic system orientation to maximize seize solar energy and produce solar electricity. All the precautions were taken to minimizing the consumption of solar energy for providing the suitable air-condition to the inhibitor of the solar house in addition to use of energy efficient appliances and consideration the practices of the individuals and communities toward transferring useful and appropriate technologies for providing the required solar electric energy